Cyberbullying and Students Engagement in School: A Literature Review - Veiga, Feliciano Henriques (2015)
Background: Cyberbullying refers to an indirect and covert form of aggression, carried out through the use of new technologies, exhibiting distinct features from those found present in traditional bullying, and has been acquiring its own space of analyses and research; still, it maintains an inevitable proximity with the second, namely, the negative impact on the victim, both the person and the student, with consequences on academic performance, among other aspects. Purpose: This piece reviews some of the most relevant studies on cyberbullying, its assessment and relation with personal (self-esteem, age, sex, ethnicity and type of aggression) and contextual (family, school context and peer group) variables, as well as with several aspect related to academic context, particularly, students‟ engagement in school and academic success. Considering the expected link between bullying and cyberbullying, some studies on the first form of aggression were included in this review, as they may be considered a theoretical referential in this subject. Conclusions: Cyberbullying is a recent and important phenomenon, linked to the inclusion of new technologies in daily life. There are, however, some gaps in research carried out on this issue, which presents different features from those that characterize traditional bullying. Similarly to bullying, studies suggest that cyberbullying presents negative impact both on students and academic success. Students‟ engagement in school plays an import role in the occurrence of aggression-victimization behaviors and appears to be a valorous strategy in cyberbullying prevention.